Optimizing the Implementation of Public Service Principles in Environmental Management at the Bima City Environmental Agency - Hendra, Hendra; Irfan, M.; Budiman, Arif; Rizkiani, Firliah; Ardyansah, Ady (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2025)
The effective implementation of public service principles is crucial in the sustainable management of environmental resources. The Environmental Agency (BLH) plays a strategic role in maintaining and improving environmental quality. This study aims to examine how public service principles are applied in environmental management by the Environmental Agency of Bima City, as well as the challenges and solutions encountered in its implementation. The research adopts a qualitative approach with a case study design, conducting interviews with BLH employees, stakeholders, and the local community. The findings indicate that although the BLH of Bima City has implemented public service principles such as accountability, transparency, and responsiveness, there are still challenges related to resources, inter-agency coordination, and public understanding. Therefore, to optimize public service in the environmental sector, it is necessary to enhance human resource capacity, improve inter-agency collaboration, and intensify public outreach on the importance of their role in environmental management.